Balancing Tourism and Conservation: The Role of Local Communities in Bali’s Ecotourism Management - Utama, I Gusti Bagus Rai; Trimurti , Christimulia Purnama; Junaedi , I Wayan Ruspendi; Krismawintari , Ni Putu Dyah (Media Konservasi, 2025)
This study examines key factors and interaction patterns influencing local community participation in Bali’s ecotourism management, responding to the persistent imbalance between tourism interests and nature conservation. It aims to provide policy and program recommendations that strengthen community roles in sustainable practices across five key sites: West Bali National Park, Buyan–Tamblingan, Bali Mangroves, Batur Kintamani, and Lembongan. This study aims to identify key factors influencing the role of local communities in Bali’s ecotourism management, providing targeted policy recommendations to enhance sustainable practices through a quantitative approach. The study utilizes structured questionnaires and direct observation among 250 residents from five different ecotourism areas. Data were analyzed using Exploratory Factor Analysis (EFA) to identify the main drivers of community involvement. The results show strong local leadership, plenty of business openings, willingness for novelty, collaboration, and environmental awareness boost the level of participation leading to economic development through social cohesion and creating long-term commitment, on which government training, technical support, and funding role necessitate sustaining ecotourism enterprises. Novelty is empirically identifying such community-based factors with their linkages toward environmental protection within the unique context of Bali.